磁场调制式永磁齿轮气隙磁密数理模型建立及其运行机理分析 - 葛研军; 刘艳龙; 赵鹏; 周凯凯 (Jixie chuandong)
In order to solve the defects that the theory about air-gap flux density for field modulated permanent magnetic gear（FMPMG）is not perfect,and unable to deeply reveal its mechanism,based on the way of calculating the air-gap flux density and unilateral slotted air-gap permeance,the systematic mathematical model about air-gap flux density is deduced and established.In the light of the model,it can produce modulating effect to internal and external rotors,and make the modulated harmonic produced by one rotor match with the fundamental wave by another rotor,meanwhile the output rotational speed and torque of FMPMG is according to the gear ratio.The modulating effect of stationary steel polepieces depends on the magnetic number of pole pairs on the rotors,the more number of pole pairs,the more its modulating effect is obvious,on the other hand,is not obvious.